Is acupoint injection the optimal way to administer mecobalamin for diabetic peripheral neuropathy? A meta-analysis and trial sequential analysis - Zhang, Fei; Yu, Yunfeng; Yin, Shuang; Hu, Gang; Yang, Xinyu; Tong, Keke; Yu, Rong (Frontiers in Neurology, 2023)
Objective: Methylcobalamin is a commonly used drug in the treatment of diabetic peripheral neuropathy (DPN). This study aimed to systematically evaluate the efficacy and safety of acupoint injection of methylcobalamin for DPN. Methods: Relevant clinical trials on acupoint injection of methylcobalamin for DPN published before January 31, 2023 were searched in 8 commonly used databases. After screening and confirming the included studies, meta-analysis and trial sequential analysis were performed. Results: 10 relevant studies were confirmed whose total sample size was 927 cases. On the efficacy endpoints, meta-analysis showed that compared with other administration methods, acupoint injection of methylcobalamin significantly increased the clinical effective rate by 27% [RR=1.